THE ADHESIONS OF PLEURAL CAVITY:CLINICAL AND MORPHOLOGICAL CHARACTERISTICS - Anton Vladimirovich Kalashnikov (Современная наука и инновации)
The article presents the results of the morphological analysis ofpleural adhesions that formed after the experimental fracture of ribs. It shows the structural changes in the adhesions according to the length of the postoperative period.